Tribological and mechanical properties of biobased reinforcement in a friction composite material - Vivek,S (2020)
ABSTRACT This work presents the function of biobased ingredients (palm fiber) as reinforcement in brake pad materials. Reinforcement in brake lining improvise wear stability, wear resistance and friction optimization under a dynamic set of operating variables such as braking force, sliding speed, braking duration and braking temperature. The effect of palm fiber on physical, mechanical and tribological properties of brake pad composite is evaluated. The percentage of palm fiber is gradually increased from 2% to 12% at an interval of 2% as an alternate of rockwool fiber by varying the pressure and speed in a pin on disc tribometer. By increasing the pressure, 8% and 10% shows high friction stability at all speeds. The results show that the raise in the palm fiber quantity increases the hardness, specific gravity and heat swell and the properties, loss on ignition and porosity decreases. The SEM descriptions of the composite indicated that the smaller micro voids occurred in the sample having low palm fiber. Weight gain in the composites were also observed by exposing them in salt water, water and oil.